2012
DOI: 10.1519/jsc.0b013e31823f29b5
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Response and Neutrophil Functions in Players After a Futsal Match

Abstract: Inflammatory response and neutrophil functions in players after a futsal match. J Strength Cond Res 26(9): 2507-2514, 2012-Futsal players suffer injuries resulting from muscle fatigue and contact or collision among players. Muscle lesions can be detected by measuring muscle lesion markers such as creatine kinase (CK) and lactate dehydrogenase (LDH) in plasma. After an initial lesion, there is an increase in the plasma levels of C-reactive protein (CRP) and proinflammatory cytokines. These mediators may activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 19 publications
3
33
0
2
Order By: Relevance
“…They act as neuroendocrine mediators, corticosteroid releasing factors, interleukin producers, and are associated with oxidation-reduction processes that produce free radicals. Several studies have shown that most components of circulating leukocytes, mainly neutrophils, increase dramatically during exercise (de Moura et al, 2012; Gavrieli et al, 2008; Kakanis et al, 2010). The magnitude of this increase is related to its duration and intensity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They act as neuroendocrine mediators, corticosteroid releasing factors, interleukin producers, and are associated with oxidation-reduction processes that produce free radicals. Several studies have shown that most components of circulating leukocytes, mainly neutrophils, increase dramatically during exercise (de Moura et al, 2012; Gavrieli et al, 2008; Kakanis et al, 2010). The magnitude of this increase is related to its duration and intensity.…”
Section: Discussionmentioning
confidence: 99%
“…This temporary depression of immune function is a result of acute exercise or competition. Acute exercise also results in an increase of leukocytes and neutrophils, which are the first to migrate to the area of injury (de Moura et al, 2012; Tossige-Gomes et al, 2014); however, lymphocyte circulation is reduced (Gleeson, 2007; Park and Park, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…It is also suggested a reduction to the frequency of high intensity microcycle throughout the season as well as to the number of weekly training sessions so as to reduce the injury risk (Medina, Lorente, Salillas, & Marqueta, in press). Concerning heamatological changes it was found that a futsal game creates inflammation, activates the neutrophils but with reduced activity and increases the concentration of the blood plasma (De Moura et al, 2012). On the other hand futsal players indicate higher level of bone density and lower osteoporosis risk (Mousavi, Khayambashi, & Rahnama, 2010;Rahnama, Bambaeichi, Khayambashi, & Jafarpour, 2009).…”
Section: Injuriesmentioning
confidence: 99%
“…The cells were then incubated for 30 min at 4 ∘ C. Ten thousand events were analyzed per sample. Fluorescence of the propidium iodide was measured using the FL2 channel (orange-red fluorescence = 585/545 nm) [18].…”
Section: Proportion Of Cells With Dna Fragmentationmentioning
confidence: 99%
“…Hydroethidine is intracellularly oxidised by oxygen radicals, being converted into ethidium bromide that tightly binds to DNA and shows a strong red fluorescence that was measured using the FL3 channel of a FACSCalibur flow cytometer (Becton Dickinson, CA, USA). Ten thousand events were analyzed per experiment [15,18].…”
Section: Flow Cytometric Measurement Of Reactive Oxygenmentioning
confidence: 99%